Resilience process of a victim sexual violence in women: Transformation from victim to activist - Inayah, Risma; Palila, Sara (Humanitas: Indonesian Psychological Journal, 2022)
Humans face numerous life challenges and phenomena that could cause traumatic feelings, such as violent cases. Amid these challenges, resilience was an essential psychological ability for individuals, including victims of sexual violence. Thus, this study aimed to determine the resilience process, factors that influenced and the meaning of the resilience process traversed by women victims of sexual violence. This research involved three informants who were victims of sexual violence. A qualitative method with a phenomenological approach was applied in this study. The semi-structured interviews were conducted in data collection. The data were analyzed with interpretative phenomenological analysis. Based on the analysis of transcribed interviews, three themes emerged: experienced various unpleasant emotions, coped and adapted with the situation, experienced several changes in herself and became resilient. Participants also have their meaning of the resilience process. Furthermore, the new finding is the pain victims experience, and their coping forces them to become resilient and join the organization that focuses on against sexual violence. Internal and external factors affect the resilience of victims, including empathy, social concern, and goals to be achieved. The implication of this study is to enhance the current literature on resilience and as additional knowledge to understand the resilience process and factors that influence victims of sexual violence to become resilient.